Characterization of three Stenotrophomonas strains isolated from different ecosystems and proposal of Stenotrophomonas mori sp. nov. and Stenotrophomonas lacuserhaii sp. nov. - Deng, Yang; Han, Xue-Fei; Jiang, Zhu-Ming; Yu, Li-Yan; Li, Yong; Zhang, Yu-Qin (Frontiers in Microbiology, 2022)
Stenotrophomonas spp. have primarily been reported as non-pathogenic, plant-probiotic bacteria, despite the presence of some opportunistic human pathogens in the genus. Here, three Gram-stain negative, rod-shaped, non-spore-forming bacteria, designated as strains CPCC 101365T, CPCC 101269T, and CPCC 101426 were isolated from surface-sterilized medicinal plant roots of a mulberry plant, freshwaterand sandy soils in the Badain Jaran desert, respectively. 16S rRNA gene sequence analysis of these isolates indicated that they belong to the genus Stenotrophomonas, with nucleotide similarities of 96.52-99.92 % to identified Stenotrophomonas members. Phylogenetic analysis based on 16S rRNA gene and genome sequences confirmed that the isolates are members of the genus Stenotrophomonas. Values for genomic average nucleotide identity (ANI) (< 95 %) and digital DNA-DNA hybridization (dDDH) (< 70 %) indicated that strains CPCC 101365T and CPCC 101269T were well-differentiated from validly described Stenotrophomonas species, while strain CPCC 101426 shared high ANI (97.7 %) and dDDH (78.3 %) with its closest phylogenetic neighbor, Stenotrophomonas koreensis JCM 13256T. The three genomes were approximately 3.1-4.0 Mbp in size and their G+C content ranged in 66.2-70.2 %, with values slightly differing between CPCC 101365T (3.4 Mbp; 70.2 %), CPCC 101269T (4.0 Mbp; 66.4 %) and CPCC 101426 (3.1 Mbp; 66.2 %). Genes encoding enzymes involved in the biosynthesis of indole-3-acetic acid and siderophores were identified in the genomes of the three isolates, suggesting that the strains might serve roles as plant-growth promoting microorganisms. The polar lipid fractions of the three isolates primarily comprised DPG, PG, and PE. The predominant cellular fatty acid was iso-C15 : 0, with moderate amounts of antesio-C15 : 0, iso-C11 : 0, iso C17 : 1 ɷ9c/C16 : 0 10-methyl, iso-C14 : 0, and C16 : 1ɷ7c/C16 : 1ɷ6c. These results indicate that polyphasic characteristics of strain CPCC 101365T and CPCC 101269T differed from other identified Stenotrophomonas species and that strain CPCC 101426 was affiliated with the species Stenotrophomonas koreensis. Two novel species of the genus Stenotrophomonas are consequently proposed, corresponding to Stenotrophomonas mori sp. nov. (type strain CPCC 101365T =DY006T= KCTC 82900T) and Stenotrophomonas lacuserhaii sp. nov. (type strain CPCC 101269T =K32T= KCTC 82901T).